Catalyzing Change Through Engaged Department Cohorts: Overcoming the One-and-Done Model - Danielle Lake; Karyn E. Rabourn; Gloria Mileva (The University of Alabama, 2022)
This article examines the merits and challenges of catalyzing institution-wide community engagement through onboarding successive engaged department cohorts. Building upon previous findings, it tests the hypothesis that deep and integrated community engagement within departments can be leveraged into pervasive engagement across an institution, exploring critical challenges to fostering collaborative, scaffolded, and sustained community engagement and offering recommendations. Such initiatives have been designed and piloted across the United States as a possible starting point for shifting often temporary, fragmented, and isolated community engagement efforts to collaborative and sustainable engagement opportunities that span programs of study. This cross-institutional and multi-departmental case study analyzes these claims, documenting the lessons learned from two successive initiatives encompassing 10 engaged departments across three institutions of higher education in the Midwest. Research harnesses traditional surveys, faculty, community, and leadership interviews, initiative reporting documents, as well as systemic action research practices. Through a cross-departmental and institutional comparison analysis, the researchers highlight the most challenging barriers and promising interventions to overcome the one-and-done model of previous engagement efforts.